Mapping Multimodal Linguistics Research: A CiteSpace Bibliometric Analysis - Lu, Yan (Forum for Linguistic Studies, 2025)
Using a bibliometric analysis with CiteSpace, this paper examines the current state and developmental trends of multimodal linguistics research, focusing on 2536 references from the Web of Science database from 2013 to 2023. The study also considers publication trends, top countries, universities and authors, as well as the frequency of most cited journals and literature, research topics and emerging hotspots. The results show that the field of multimodal research has grown rapidly over the last ten years, with an average annual growth rate of 38% and a peak of 435 publications in 2023,demonstrating its rapid expansion in linguistics. Research hotspots include multimodal discourse analysis, visual grammar,multimodal pedagogical applications, social semiotics and multimodal cognition and perception. The field exhibits strong interdisciplinary characteristics, such as the integration of social semiotics with cognitive linguistics and the application of digital technologies. It can be stated that multimodal research is developing into a more integrated and interdisciplinary approach, reflecting the complex and dynamic nature of communication in today’s world. Future research should focus on cross-cultural variations in modal usage, the construction of multimodal grammatical systems, and innovative applications in educational contexts. This research provides quantitative evidence for understanding the knowledge map of multimodal studies, offering insights for future research directions and methodological advancements.